2022
DOI: 10.3390/ijms232213964
|View full text |Cite
|
Sign up to set email alerts
|

Generation of the First Human In Vitro Model for McArdle Disease Based on iPSC Technology

Abstract: McArdle disease is a rare autosomal recessive disorder caused by mutations in the PYGM gene. This gene encodes for the skeletal muscle isoform of glycogen phosphorylase (myophosphorylase), the first enzyme in glycogenolysis. Patients with this disorder are unable to obtain energy from their glycogen stored in skeletal muscle, prompting an exercise intolerance. Currently, there is no treatment for this disease, and the lack of suitable in vitro human models has prevented the search for therapies against it. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Recently, in our laboratory, we obtained, for the first time, a human skeletal muscle model of McArdle disease, based on the use of iPSC technology. This model harbours the most frequent pathogenic variant in the Caucasian population in the PYGM gene, NM_005609.4: c.148C>T (p.Arg50Ter) [ 8 ]. Here, we present the generation of a human iPSC-based skeletal muscle model of McArdle disease carrying the second most frequent pathogenic variant in the Spanish population in the PYGM gene, NM_005609.4: c.2392T>C (p.Trp798Arg).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in our laboratory, we obtained, for the first time, a human skeletal muscle model of McArdle disease, based on the use of iPSC technology. This model harbours the most frequent pathogenic variant in the Caucasian population in the PYGM gene, NM_005609.4: c.148C>T (p.Arg50Ter) [ 8 ]. Here, we present the generation of a human iPSC-based skeletal muscle model of McArdle disease carrying the second most frequent pathogenic variant in the Spanish population in the PYGM gene, NM_005609.4: c.2392T>C (p.Trp798Arg).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group reported the generation of the first human in vitro skeletal muscle model of McArdle disease based on iPSC technology [ 8 ]. This model was obtained from a patient harbouring the most common genetic defect in the PYGM gene described in the Caucasian population: NM_005609.4: c.148C>T (p.Arg50Ter).…”
Section: Introductionmentioning
confidence: 99%
“…McArdle disease [146], carnitine palmitoyltransferase II (CPT II) deficiency [147] and nemaline myopathy [148], allowing for a good replication of the main disease-related pathological features.…”
Section: Hipscs Organoids and Novel Platforms For Neuromuscular Disor...mentioning
confidence: 99%
“…RTC14 increased mRNA expression of the XPC gene and NAGLU gene in fibroblasts from xeroderma pigmentosum group C and Sanfilippo C patients, respectively [ 160 ]. However, RTC13 or RTC14 could not suppress PTCs associated with hemophilia A, McArdle disease, chronic granulomatous disease, and Wiscott-Aldrich syndrome [ 159 , 161 , 162 , 163 ]. A study of the SAR of RTC13 revealed that several derivatives containing variations on both aryl and thiazolidinone rings exhibited good readthrough activity.…”
Section: Non-aminoglycoside Tridsmentioning
confidence: 99%